A methodical approach to the pre-match training of goalkeepers in beach soccer - Privalov, A. V.; Nifontov, M. Yu.; Mukhamedzyanov, R. R.; Dmitriev, I. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to creation and validation of a holistic framework for the training of elite goalkeepers in beach soccer prior to competitions.